How the verb works in Arabic-speaking aphasics - BADAOUI, Fouzia (Journal of Human Sciences, 2022)
The aim of this research is to analyze the event and time in the use of verb in Arabic-speaking aphasia sufferers to extract the characteristics that characterize the grammatical processes exploited by them in applying the derivation from the past to the present tense in correct verbs and impaired verbs. We have implemented a series of tests. The results showed the presence of disturbance in the walls of the floor of the person with Vernicke’s aphasia, and a disorder in employing the example in Broca’s aphasia.